Current Practices and Recommendations for Children with Food Allergies and Feeding Behaviours: Insights from a Survey Among Australian Health Professionals - Jennifer Kefford; Rebecca L. Packer; Merryn Netting; Elizabeth C. Ward; Jeanne Marshall (Children)
Background: Children with food allergies can present with paediatric feeding disorder (PFD). However, access to coordinated multidisciplinary services to support these children in Australia is inconsistent. To date, the availability of services or the perceived care needs of Australian health professionals working with this population have not been formally explored. Methods: A web-based survey was distributed to health professionals in Australia. Quantitative demographic data were summarised using descriptive statistics, and open-ended responses were analysed using content analysis. Results: The final sample comprised 98 responses, with speech pathologists representing the largest professional group (n = 39; 40%). A majority (59%) worked in hospital-based services. Open-ended responses were coded utilising content analysis. Three categories were developed including (1) service delivery, (2) intervention, and (3) resources. Services were commonly impacted by long wait times, limited staff training, and inconsistencies between hospital and community care. Additionally, mental health support was frequently reported as insufficient. Conclusions: The findings from this study underscore the need for integrated services for children with food allergies and paediatric feeding disorder. Recommended areas for future research include exploring caregiver perspectives and the impact of food allergies and paediatric feeding disorder, and consideration of co-designed studies to inform service improvement initiatives.